Blockade of β-Adrenergic Receptors by Propranolol Disrupts Reconsolidation of Drug Memory and Attenuates Heroin Seeking - Chen, Liangpei; Huang, Shihao; Yang, Chang; Wu, Feilong; Zheng, Qiuyao; Yan, He; Yan, Jie; Luo, Yixiao; Galaj, Ewa (Frontiers in Pharmacology, 2021)
Persistent traces of drug reward memories contribute to intense craving and often trigger relapse. A number of pharmacological interventions on drug-associated memories have shown significant benefits in relapse prevention at a preclinical level but their translational potential is limited due to deleterious side effects. Propranolol, a non-specific β-adrenergic receptors antagonist, is known for its ability to erase maladaptive memories associated with nicotine or cocaine in rodents and humans. However, little is known about its effect on reconsolidation of heroin memory and heroin seeking. In the present study, rats with a history of intravenous heroin self-administration received the propranolol treatment (10 mg/kg; i.p.) at different time windows with or without CS (conditioned stimulus) exposure. Our results showed that propranolol, when administered immediately after CS exposure but not 6 h later, can significantly attenuate cue-induced and drug-primed reinstatement of heroin seeking, suggesting that propranolol has the ability to disrupt heroin memory and reduce relapse. The propranolol treatment without retrieval of drug memory had no effect on subsequent reinstatement of heroin seeking, suggesting that its interfering effects are retrieval-dependent. Importantly, the effects of propranolol were long lasting as rats showed diminished drug seeking even 28 days after the treatment. Altogether, our study suggests that propranolol can interfere with reconsolidation of heroin memory and reduce subsequent drug seeking, making it an attractive therapeutic candidate for the treatment of opioid addiction and relapse prevention.